(untitled) (International Journal of Engineering and Computer Science, 2017)
The dropped-call rate (DCR) is the fraction of the telephone calls which, due to technical reasons, were cut off before the speaking parties had finished their conversational tone and before one of them had hung up (dropped calls) This fraction is usually measured as a percentage of all .CDR is defined as the ratio of abnormal disconnect of calls to total calls established. The performance of a TSP relating to call drop is assessed through this parameter. The benchmark set by TRAI for CDR is <2%.Since the CDR for the service area as a whole does not reveal the extent of number of areas or localities where the CDR is poor, the Authority is monitoring another parameter called “Worst affected cells” in which the call drop rate exceeds 3% during cell busy hour, averaged over a month for a service area ” provides a much more localised view of the network. In this paper we have suggested a forced handoff method (Directed Retry)for cells going down due to weak transmission plan or other reason to reduce call drops